PERAN NOTARIS DAN PPAT DALAM MENGOPTIMALKAN PENYELENGGARAAN RUMAH SUSUN DI INDONESIA - Ananda Yunne Pangerti Ningtyas; Liza Priandhini (PALAR (Pakuan Law review), 2022)
AbstractThe management of flats is one of the government ways to provide opportunities for the community to have a decent, good, and healthy place to live as mandated by Article 28H paragraph (1) of the 1945 Constitution. The government has built flats, but they have not been implemented optimally, as evidenced by the high number of abandoned flats. The Abandoned flats happen because parties do not perform the maintenance of the flat following the statutory regulations. The operation of flats has been regulated by Law Number 20 of 2011 on Flats, whereas its administration is regulated by Government Regulation Number 13 of 2021. Notaries and PPAT have critical roles as public officials who make an authentic deed to a legal act, namely the sale and purchase agreement (PPJB) and the sale and purchase deed (AJB). Notaries can assist in the maintenance of flats with the establishment of Regulation of the Minister of Public Works and Housing number 11/PRT/M/2019 on the Pre -Sale and Purchase Agreement System, thus the Ministerial Regulation can be used as a guideline by Notaries in making PPJB. PPAT in making AJB must also understand the form of proof of ownership of the apartment unit. Notaries in carrying out their duties and authorities must be in accordance with the Notary Office Law and the Notary Code of  Keywords :Management of flat, Notary, PPAT AbstrakPenyelenggaraan rumah susun merupakan salah satu cara pemerintah dalam memberikan kesempatan kepada masyarakat untuk memiliki tempat tinggal yang layak, baik dan sehat sebagaimana diamanatkan oleh Pasal 28H ayat (1) Undang-Undang Dasar 1945. Pemerintah telah melakukan penyelenggaraan rumah susun namun belum terlaksana secara optimal dengan tingginya kasus rumah susun yang terbengkalai. Rumah susun yang terbengkalai disebabkan para pihak yang tidak melakukan penyelenggaraan rumah susun sesuai dengan peraturan perundang-undangan. Penyelenggaraan rumah susun telah diatur dengan Undang-undang Nomor 20 Tahun 2011 tentang Rumah Susun dan peraturan pelaksanaannya diatur dengan Peraturan Pemerintahan Nomor 13 Tahun 2021 tentang Penyelenggaraan Rumah Susun. Notaris dan PPAT memiliki peran penting sebagai pejabat umum yang membuat akta autentik terhadap suatu perbuatan hukum, yakni perjanjian pengikatan jual beli (PPJB) dan akta jual beli (AJB). Notaris dapat membantu penyelenggaraan rumah susun dengan dibentuknya Peraturan Menteri Pekerjaan Umum dan Perumahan Rakyat nomor 11/PRT/M/2019 tentang Sistem Perjanjian Pendahuluan Jual Beli Rumah, dengan demikian  Peraturan Menteri tersebut dapat dijadikan pedoman oleh notaris dalam membuat PPJB. PPAT dalam membuat AJB juga harus memahami bentuk bukti kepemilikan atas satuan rumah susun. Notaris dalam melaksanakan tugas dan wewenangnya harus sesuai dengan Undang-Undang  Jabatan Notaris dan Kode Etik Notaris. Kata kunci: Penyelenggaraan Rumah Susun;  Notaris;  PPAT.